The impact of communication approach towards stakeholder management in construction industry - Hasli Azilla, Hamzah (2014)
The communication approach chosen for communicate medium among stakeholder as vital for effective communication. This study is to identify the medium of communication that commonly used by the organization in managing their stakeholder and determine the impact of communication to stakeholder management. Both of the objectives have huge influence to ensure a success of the project. Therefore, medium of communication also give an impact towards the company on how they managing their stakeholder. Wrong chosen of communication can affected the stakeholder satisfaction, cause problems such as misunderstanding and misinterpretation between stakeholder and the organization. The population of this study is 75 contractor under Grade 7 registered with Construction Industry Development Board of Malaysia (CIDB) at Kuantan, Pahang Darul Makmur. The sample size is use as the units of analysis, 63 contractors which were from executive position was selected. In conducting this study, random sampling survey method was being used and this questionnaires survey was distributed to respondent by email and face to face. For data analyzing, this data was carried out by using Descriptive statistic is drawn from Statistical Package Social Science (SPSS) outputs. The finding from this study indicate that the medium of communication have an impact towards stakeholder management and lead to the problem to the project